Liberalism, fascism, or social democracy : social classes and the political origins of regimes in interwar Europe - Luebbert, Gregory M. (Oxford University Press, 1991)
This work provides a sweeping historical analysis of the political development of Western Europe in the late nineteenth and early twentieth century. Arguing that the evolution of most Western European nations into liberal democracies, social democracies, or fascist regimes was attributable to a discrete set of social class alliances, the author explores the origins and outcomes of the political development in the individual nations. In Britain, France, and Switzerland, countries with a unified middle class, liberal forces established political hegemony before World War I. By coopting considera.